(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article serves as a report and reflection on the university community engagement program Time of impermanence: theater in female prisons in Rio Grande do Sul, which was developed in 2018 at the Montenegro Modulated Penitentiary and the Torres Female State Prison by the theatre teacher training course at the Universidade Estadual do Rio Grande do Sul. Using references from theater, philosophy, and the social sciences and analyzing the notion of space, we reflect on the impact of theater in prison. The project consisted of presentations from the play The Cherry Orchard, discussions, theatrical workshops and other activities with incarcerated women.